Answer:
The first derivative of
(r(t)=5*t^{-2}) with respect to t is
(r'(t) = -10*t^{-3}).
Explanation:
Let be
, which can be rewritten as
. The rule of differentiation for a potential function multiplied by a constant is:
,
![\forall \,n\\eq 0](https://img.qammunity.org/2021/formulas/mathematics/high-school/81cljeo9i8h9xifh4y8libnuaozncrzzoj.png)
Then,
![r'(t) = (-2)\cdot 5\cdot t^(-3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/kegdlk02q83ej3v35bqfafvppd3lrxbg32.png)
(r'(t) = -10*t^{-3})
The first derivative of
(r(t)=5*t^{-2}) with respect to t is
(r'(t) = -10*t^{-3}).